2002
DOI: 10.1177/14746514020020011801
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipids and antidiabetic agents: a brief overview

Abstract: Ben Keiden and colleagues offer a transatlantic view of the effect of antidiabetic medications on plasma lipids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
5
12
1
Order By: Relevance
“…Addition of metformin not only decreased the total cholesterol levels but also had a positive effect on the distribution of cholesterol between HDL (increase) and LDL lipoproteins (decrease). The results were in agreement with the combined therapy with metformin plus bedtime insulin injections that showed beneficial effects on decreasing levels of LDL [86]. But mean values of lipid profiles (TC, LDL and TG) were higher among patients receiving combination therapy of insulin plus metformin than those receiving metformin plus glibenclamide receiving group but not statistically Table 3: Biochemical characteristics of patients who were receiving insulin and glibenclamide.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Addition of metformin not only decreased the total cholesterol levels but also had a positive effect on the distribution of cholesterol between HDL (increase) and LDL lipoproteins (decrease). The results were in agreement with the combined therapy with metformin plus bedtime insulin injections that showed beneficial effects on decreasing levels of LDL [86]. But mean values of lipid profiles (TC, LDL and TG) were higher among patients receiving combination therapy of insulin plus metformin than those receiving metformin plus glibenclamide receiving group but not statistically Table 3: Biochemical characteristics of patients who were receiving insulin and glibenclamide.…”
Section: Discussionsupporting
confidence: 78%
“…This could be due to non-compliance of patients. The present work is not in agreement with the reported values of insulin therapy by Keidan et al [86] that showed LDL and TC levels were static but HDL levels were elevated. It was found that insulin therapy do not beneficially affect lipid levels leading to a reduction in triglyceride levels.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The changes in lipid profile of diabetic patients are associated with increased free fatty acid flux and secondary to insulin resistance [36,37]. Standard drug metformin is known to have a beneficial effect in decreasing the level of triglycerides and LDL-cholesterol by 10-15% along with slight increase in HDL levels [38]. Hence, the observed effect of metformin on lipid profile of diabetic rats is in agreement with the property of the drug.…”
Section: Discussionsupporting
confidence: 71%
“…There were trends towards a decrease, but no significant changes were observed in triglycerides, cholesterol, and LDL levels with resveratrol supplementation, while a significant increase in LDL levels was observed in the control group. Metformin, glibenclamide, and insulin are all known to have beneficial or no effect on the lipid profiles [42]; therefore, other independent factors may have contributed to the observed increase in the control group. …”
Section: Discussionmentioning
confidence: 99%